DEFICIENCY OF γδ T-LYMPHOCYTES CONTRIBUTES TO MORTALITY AND IMMUNOSUPPRESSION IN SEPSIS - Chung, Chun-Shiang (2006)
Studies have indicated that γδ T-lymphocytes play an important role in the regulation of immune function and the clearance of intracellular pathogens. We have recently reported that intraepithelial lymphocytes (IEL), which is rich in γδ T-cells, within the small intestine illustrated a significant increase in apoptosis and immune dysfunction in mice subjected to sepsis. However, the contribution of γδ T-cells to the host response to polymicrobial sepsis remains unclear. In this study, we initially observed that following sepsis induced by cecal ligation and puncture (CLP) there was an increase in small intestinal IEL CD8(+)-γδ(+) T-cells in control γδ +/+ mice. Importantly, we subsequently found an increased early mortality in mice lacking γδ T-cells (γδ −/−) after sepsis. This was associated with a decrease in plasma TNF-α, IL-6 and IL-12 levels in γδ −/− mice compared to γδ +/+ mice after sepsis. In addition, even though in vitro LPS-stimulated peritoneal macrophages showed a reduction in IL-6 and IL-12 release after CLP, these cytokines were less suppressed in macrophages isolated from γδ −/− mice. Alternatively, IL-10 release was not different between septic γδ +/+ and γδ −/− mice. While Th1 cytokine release by anti-CD3-stimulated splenocytes was significantly depressed in septic γδ +/+ mice, there was no such depression in γδ −/− mice. However, γδ T-cell deficiency had no effect on Th2 cytokine release. These findings suggest that γδ T-cells may play a critical role in regulating the host immune response and survival to sepsis, in part by alteration of the level of IEL CD8(+)-γδ(+) T-cells and through the development of Th1 response.